PERKECAMBAHAN BIJI DAN PERKEMBANGAN DAUN NYAMPLUNG (Calophyllum inophyllum L.) - , NURHAYANTI, S.Pd, Prof. Dr. Issirep Sumardi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nyamplung (Calophyllum inophyllum L.) is a plant which widely cultivated because its organ have multi purposes :biofuels, medicine, biobricket industry, and mixture of fragrances hair. The organs of this plant contain a variety of metabolites, usually stored in a cell, space, glands, or secretory channels. Cultivation of the plants still face a problem since the seeds structure are very hard therefore, it takes a long time to germinate. The aims of the study: to find out the quickest method of seed germination, tracing the leaf development, secretory tissue distribution and the structure of stomata appropriate of leaf development. There were 4 methods to determine the germination of seeds. Observation of leaf development and distribution of tissue secretory using permanent preparations, while the structure of the stomata with the manufacture of semi-permanent preparations. Samples of leaf buds,young leaves, mature, and old leaves were grouped into 10 groups from 20 mounth old plant. Colecting datas is from the seed germination and leaf development analysis by quantitative and qualitative. Analysis of data is by comparing between groups of samples. Data analysis by ANOVA, followed DMRT test at 5% significance level. The statistics calculation is using SPSS 16 statistical package. The results showed that the fastest germination of seeds was 4 method (without seed coat). The leaf development begins with the formation of leaf butress developing into midvein, followed by formation of two leaf panels, plate meristem developing into leaf blade perfectly. Secretory tissue is higher in midvein more than in the leaf lamina, the number increased with leaf development. The secretory type is secretory glands. The development of stomata starts from the initial cells divisions, resulting a part of guard cell with a pair of round cells then become cells the type of kidney, the number of neighboring cells is 4-5 to form a flat edge-notched texture. The stomata type is anomocityc.